Regulatory Model of Cash Waqf within the National Legal System and Its Challenges - Nova Monaya; Andri Brawijaya (Jurnal Legisci, 2025)
Background. Cash waqf has emerged as an important instrument for social and economic development, yet its regulatory framework within the national legal system remains fragmented and inconsistently applied. Aim. This study aims to analyze the structure, effectiveness, and gaps of the current regulatory model governing cash waqf while identifying the challenges faced by key stakeholders. Methods. A qualitative legal approach is used, combining statutory analysis, case studies, and interviews with regulators and waqf managers to evaluate how existing norms function in practice. Results. The study finds that although the legal framework provides a formal foundation for cash waqf management, several issues persist, including overlapping authorities, weak enforcement mechanisms, and limited institutional capacity. Conclusions. A more coherent, integrated, and adaptive regulatory model is required to strengthen legal certainty and improve institutional performance in managing cash waqf. Implication. The findings underscore the need for policymakers, regulators, and waqf institutions to refine governance standards, enhance coordination, and adopt technological innovations to ensure transparent and efficient cash waqf administration. Keywords: Cash Waqf, Regulatory Model, National Legal System, Governance, Legal Challenges, Waqf Institutions